2021
DOI: 10.3389/fcell.2021.667435
|View full text |Cite
|
Sign up to set email alerts
|

The Absence of PTEN in Breast Cancer Is a Driver of MLN4924 Resistance

Abstract: Background: Numerous studies have indicated that the neddylation pathway is closely associated with tumor development. MLN4924 (Pevonedistat), an inhibitor of the NEDD8-activating E1 enzyme, is considered a promising chemotherapeutic agent. Recently, we demonstrated that neddylation of the tumor suppressor PTEN occurs under high glucose conditions and promotes breast cancer development. It has been shown, however, that PTEN protein levels are reduced by 30–40% in breast cancer. Whether this PTEN deficiency aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…MLN4924 overactivated the AKT pathway in a feedback manner to promote the survival signaling in sheep follicular GCs, which could also lead to MLN4924 resistance to apoptosis; similar findings have been confirmed in other studies (Chen et al, 2018;Fujita et al, 2006;Mao et al, 2019;Shi et al, 2006). A highthroughput RNA-Seq study found that FOXO1 was upregulated upon MLN4924 treatment (Du et al, 2021), and our results also found an upregulation of FOXO1 that could promote sheep follicular GCs apoptosis. However, the expression of phosphorylated FOXO3a at Thr32 was downregulated by MLN4924 treatment, which could be due to the over-activation of AKT inhibiting FOXO3a transactivation (Wang et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…MLN4924 overactivated the AKT pathway in a feedback manner to promote the survival signaling in sheep follicular GCs, which could also lead to MLN4924 resistance to apoptosis; similar findings have been confirmed in other studies (Chen et al, 2018;Fujita et al, 2006;Mao et al, 2019;Shi et al, 2006). A highthroughput RNA-Seq study found that FOXO1 was upregulated upon MLN4924 treatment (Du et al, 2021), and our results also found an upregulation of FOXO1 that could promote sheep follicular GCs apoptosis. However, the expression of phosphorylated FOXO3a at Thr32 was downregulated by MLN4924 treatment, which could be due to the over-activation of AKT inhibiting FOXO3a transactivation (Wang et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, counting factor-associated protein D (CfaD), which is a secreted quorum sensing protein that modulates cell proliferation, was detected in the FbxD interactome ( Figure 6 ; Bakthavatsalam et al, 2008 ; Sheikh et al, 2015 ). These findings indicate a conserved role for neddylation in regulating cell proliferation and support recent work linking neddylation to the proliferation of cancer cells ( Du et al, 2021 ; Zhang et al, 2021 ). However, whether MLN4924 specifically affects CRLs in D. discoideum remains to be determined since non-cullin targets of neddylation have been reported in several organisms including S. pombe , A. thaliana , and Trypanosoma brucei ( Girdwood et al, 2012 ; Enchev et al, 2015 ; Mergner et al, 2015 ; Liao et al, 2017 ).…”
Section: The Roles Of Cullins and Their Regulation During D...supporting
confidence: 89%
“…Moreover, high level NEDDylation of PTEN in BC patients correlated with poor overall survival, indicating that PTEN NEDDylation might function as a prognostic marker ( Xie et al, 2021b ). Very recently, it has been reported that high glucose concentrations trigger PTEN NEDDylation and nuclear import and promote tumor development ( Du et al, 2021 ).…”
Section: Sumoylation and Neddylation Of Tumor-related Proteinsmentioning
confidence: 99%
“…Another study reported about the resistance to MLN4924, a selective inhibitor of NAE1 and thus of the NEDDylation modification ( Soucy et al, 2009 ), treatment in cancer patients with complete loss of PTEN, indicating that PTEN is necessary for MLN4924 suppression of tumor growth and that PTEN status is useful to discriminate MLN4924-responsive BC patients ( Du et al, 2021 ).…”
Section: Sumoylation and Neddylation Of Tumor-related Proteinsmentioning
confidence: 99%